2000
DOI: 10.1046/j.1365-2893.2000.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine–high dose interferon combination therapy for chronic hepatitis B patients co‐infected with the hepatitis D virus

Abstract: Currently, the best option for patients with hepatitis delta is interferon alpha therapy for at least one year. To evaluate the effect of the combination lamivudine-high-dose interferon alpha therapy, we first treated eight patients with chronic hepatitis delta infection with lamivudine for at least 24 weeks; then lamivudine was combined with a high dose of interferon alpha followed by a regular dose (9 MU tiw). Follow-up was 12 weeks. Virological, biochemical and histological features were evaluated for respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 24 publications
0
39
0
6
Order By: Relevance
“…It efficiently reduces HBV viremia but not HBsAg levels and has no effect on hepatitis delta, even when associated to IFN [50]. We treated 11 patients in whom HBV was dominant with high HBV DNA (from 10 5 to 10 8 copies/ml) and high ALT levels (mean, 513 ± 837 U/l; Table 2 Combination therapy for dual hepatitis B and C viruses infection range, 112-2973 U/l) using lamivudine 100 mg daily for a mean period of 7 months (6-24 months).…”
Section: Lamivudine With or Without Ifn Combination Therapymentioning
confidence: 99%
“…It efficiently reduces HBV viremia but not HBsAg levels and has no effect on hepatitis delta, even when associated to IFN [50]. We treated 11 patients in whom HBV was dominant with high HBV DNA (from 10 5 to 10 8 copies/ml) and high ALT levels (mean, 513 ± 837 U/l; Table 2 Combination therapy for dual hepatitis B and C viruses infection range, 112-2973 U/l) using lamivudine 100 mg daily for a mean period of 7 months (6-24 months).…”
Section: Lamivudine With or Without Ifn Combination Therapymentioning
confidence: 99%
“…Lau et al reported that interferon was effective against chronic HDVhepatitis after 12 years of therapy (19). Recently, it has been reported that combination therapy with interferon and lamivudine was effective against chronic hepatitis B with HDV co-infection (20). Consequently, we conclude that additional administration of interferon should be considered in the present case, if hepatitis flares are repeated and progression of hepatic fibrosis is predicted.…”
Section: Discussionmentioning
confidence: 55%
“…Ribavirin as a monotherapy or in combination with IFN could not show a benefit [42,45,46] , likewise Famciclovir [47] and acyclovir [48] had no effect. Different studies could not show an advantage of lamivudine as a monotherapy or combination therapy [36,49,50] . Because of a significant decrease in cccDNA levels accompanied with a reduction in serum HBsAg titers in long-term adefovir therapy [51] , the well-known HBV-effective nucleotide analogue adefovir dipivoxil was thought to be a potential anti-HDV drug as well.…”
Section: Treatment Of Delta Hepatitismentioning
confidence: 99%